PFL-lectin regulates the expression of apoptosis-related proteins to antecedent apoptosis in A549 and HT29 cells - Arul Kumar Murugesan; Malairaj Sathuvan; Anand Javee (Advances in Cancer Biology - Metastasis, 2023)
A potential treatment approach to treat this terminal illness is the mushroom-based lectin carrier system. It has been hypothesized that lectin-induced apoptotic nature causes necrosis, which leads to cell death, in cancer cells. The antibacterial and free radical scavenging capabilities of lectins were examined, according to the findings of our earlier lectin purification research. The goal of the current investigation is to determine whether Pleurotus flabellatus lectin (PFL-L) has any anti-cancer activity against colorectal cancer (HT29) and lung cancer (A549) cell lines. According to the findings of an in vitro cell line investigation, pre-treatment of the HT29 and A549 cell lines with PFL-L (10–100 μg/ml) significantly reduced the induction of apoptosis with an IC50 range of PFL-L (67 & 60 μg/ml). PFL-L protects cells against cancer cells, according to a confocal microscope viability examination of A549 and HT29 cells, and a comet test was used to track induced apoptosis. Our findings imply that PFL-L has promising anti-cancer activity and targets several apoptotic-related processes present in the A549 and HT29 cells. Additionally, when compared to the control, PFL-L increased DNA damage and the potential loss of cancer cells. A549 and HT29 cells also showed signs of the increased apoptosis-related proteins Bcl-Xl, Bcl-2, Procaspase-3, Procaspase-9, MMP-3, MMP-9, B6, N-Cadherin, and E-Cadherin. Western blot examination revealed decreased expression of apoptosis-related proteins. The results of this study demonstrate that PFL-L has anti-cancer properties against induced apoptosis in an in vitro model of A549 and HT29 cells.